Clinical practice guideline for the prevention and management of peritoneal dialysis associated infections in children: 2024 update - Warady, Bradley A.; Same, Rebecca; Borzych-Duzalka, Dagmara; Neu, Alicia M; El Mikati, Ibrahim; Mustafa, Reem A; Begin, Brandy; Nourse, Peter; Bakkaloglu, Sevcan A; Chadha, Vimal; Cano, Francisco; Yap, Hui Kim; et al. (Peritoneal dialysis international, 2024)
Infection-related complications remain the most significant cause for morbidity and technique failure in infants, children and adolescents who receive maintenance peritoneal dialysis (PD). The 2024 update of the Clinical Practice Guideline for the Prevention and Management of Peritoneal Dialysis Associated Infection in Children builds upon previous such guidelines published in 2000 and 2012 and provides comprehensive treatment guidance as recommended by an international group of pediatric PD experts based upon a review of published literature and pediatric PD registry data. The workgroup prioritized updating key clinical issues contained in the 2012 guidelines, in addition to addressing additional questions developed using the PICO format. A variety of new guideline statements, highlighted by those pertaining to antibiotic therapy of peritonitis as a result of the evolution of antibiotic susceptibilities, antibiotic stewardship and clinical registry data, as well as new clinical benchmarks, are included. Recommendations for future research designed to fill important knowledge gaps are also provided.